An Ethnographic Account of Doing Survey Research in Prison: Descriptions, Reflections, and Suggestions from the Field - Sutton, James (Qualitative Sociology Review, 2011)
This article presents an ethnographic account of my day-to-day experiences as a survey researcher in men’s prisons in the United States. I outline challenges I encountered in the field and share personal reflections on interviewing people who are incarcerated. I then put forth a series of implications and suggestions for those who plan to conduct similar studies. Researchers’ firsthand accounts of the data collection process and research settings are crucial because they provide instruction for other scholars. Yet, these aspects of doing research are conventionally ignored in survey researchers’ scholarly publications. Accordingly, this article presents an examination of my work as a survey researcher through an interpretive frame, calls for reflective approaches to conducting quantitative research, and provides a primer on doing research in prison settings.